Extent of Knowledge of Fish farmers about Scientific Fish Culture Practices in North 24 Parganas of West Bengal, India - B. Goswami, S.B. Mukhopadhyay and S.S. Dana, (Indian Journal of Extension Education, 2017)
The study was conducted in North 24 Parganas district of West Bengal. It was found that majority of the fishfarmers (50.8%) had the medium level of knowledge regarding scientific fish culture practices. The highest extent ofknowledge was observed in the names of some aquatic weeds (95.83%), and lowest was observed in the minimumdepth of water required for fish culture and the time gap required between manure application and stocking of fishseed (26.67%). The path analysis indicated that innovative proneness was the most potent variable in effecting theknowledge of fish farmers positively.